PENGARUH ORIENTASI BELANJA KONSUMEN TERHADAP MINAT PEMBELIAN SECARA ONLINE - Rena Feri Wijayanti; Joni Dwi Pribadi; Lina Budiarti (Adbis: Jurnal Administrasi dan Bisnis, 2018)
The purpose of this study is to analyze consumer motivation, especially consumers with an interest in buying online. The research was conducted by distributing questionnaires with the target of respondents in their teens who were actively using internet facilities. Based on the results of research findings consumer shopping orientation is influenced by prices which have a significant influence on purchase interest while motivation in terms of product categories does not significantly influence the interest in online purchases.